Eksplorasi Kultural Pawai Ogoh-Ogoh di Kota Malang: Implikasi untuk Integrasi Budaya dalam Pembelajaran Bahasa Indonesia - Malikha, Usrin (Universitas Al-Qolam Malang, 2024)
This study aims to explore the cultural values embedded in the Ogoh-Ogoh parade tradition in Malang City and examine its implications for cultural integration in Indonesian language learning. Originally part of the Balinese Nyepi celebration, the Ogoh-Ogoh tradition has evolved and been adopted in various regions, including Malang, with its own unique local adaptations. Using a descriptive qualitative approach, data were collected through observation, interviews, and documentation involving cultural practitioners, educators, and local communities. The findings reveal that the Ogoh-Ogoh parade encompasses values of aesthetics, tolerance, creativity, and communal spirit, which can be meaningfully integrated into Indonesian language teaching, particularly in reinforcing cultural awareness and local wisdom. This integration enriches language learning by extending beyond linguistic competence to include character development and intercultural understanding. Therefore, local traditions such as Ogoh-Ogoh can serve as contextual, relevant, and inclusive learning resources in national education.